1977
DOI: 10.2118/6129-pa
|View full text |Cite
|
Sign up to set email alerts
|

Injection Profile Effects Caused by Gravity Segregation in the Wellbore

Abstract: A discussion of remedies for many placement problems that are caused by gravity segregation of fluids in the wellbore, particularly in stimulation or workover jobs involving small treatment volumes. Three examples are given to illustrate theoretical and experimental models to find remedies for several typical fluid placement problems. Introduction Success of stimulation and workover jobs involving acid. solvents, inhibitors, or other chemicals often is determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[129][130][131][132][133][134][135][136][137] Opposed Cup Packer or Perforation Wash Tool. Selection is based on wellbore hardware, formation characteristics, and field experience.…”
Section: Well Preparationmentioning
confidence: 99%
“…[129][130][131][132][133][134][135][136][137] Opposed Cup Packer or Perforation Wash Tool. Selection is based on wellbore hardware, formation characteristics, and field experience.…”
Section: Well Preparationmentioning
confidence: 99%
“…Such models, however, neglect any wellbore effects because they assume that the acid and diverter reach all zones at the same time. Wellbore effects from gravity segregation have been modeled for particulate materials in vertical wells, 16,17 but these models are not applicable to singlephase fluids in horizontal wells. For vertical wells with short, homogeneous intervals, neglecting wellbore effects may well be a reasonable assumption for single-phase fluids.…”
Section: Review Of Acid-diversion Models Used By Previous Authorsmentioning
confidence: 99%
“…However, less attention has been given to the same displacement phenomena that occur in the near-wellbore region during small-volume chemical treatments (sand consolidation, acidization, selective plugging, etc.). Attention has been drawn to the need for more consideration of placement profiles in these operations.1O Experimental and theoretical studies 10,11 have shown that gravity segregation between fluids of different densities in the well is an important factor affecting injection profiles. The experiments described in this paper examined the effect of fluid viscosity contrast and injection rates on the placement profile of the injected fluid in the near-wellbore region of the formation.…”
Section: Introductionmentioning
confidence: 99%